(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Patients suffering from chronic pain and inflammatory disorders need novel COX-2 inhibitors to be developed with minimum toxicity to the kidneys, heart, and gastrointestinal tract and with excellent anti-inflammatory activity. The current study centers on an array of 1,4,5-trisubstituted pyrazoles produced via the reaction of ditosylates of chalcones with hydrochloride salt of phenylhydrazine. Chalcone was reacted with HTIB to produce a variety of derivatives of α, β chalcone ditosylates. Phenylhydrazine hydrochloride treatment of these chalcone ditosylates produced distinct 1,4,5-trisubstituted pyrazoles. The conversion process is mediated by 1,2-aryl migrations. IR, 1NMR, and elemental analysis were used to characterize the compounds after they had been purified by recrystallization. Using ascorbic acid as a reference, the DPPH (1,1-diphenyl-2-picrylhydrazyl) technique was used to assess the compounds' in vitro antioxidant activity. The paw edema technique caused by Carrageenan was utilized to assess the compounds' in vivo anti-inflammatory properties. The standard medication used was diclofenac sodium. A plethysmograph was used to measure the volume of the rats' paws. When compared to the standard, the compounds V5D5PH5 and V7D7PH7 showed modest antioxidant activity. When the synthetic pyrazoles were examined for their in vivo anti-inflammatory properties, substances V4D4PH4 and V7D7PH7 outperformed the reference. Here, we attempted to create new, safe, and effective drugs for the treatment of inflammatory disorders and pain by utilizing synthetic pyrazole moiety derivatives. Simple experimentation is used in the proposed study to improve pharmacological activity and yields. In the near future, chalcone ditosylate derivatives will be a powerful tool for selective modification.